The Importance of Reverberation for the Design of Neonatal Incubators - Puyana-Romero, Virginia; Núñez-Solano, Daniel; Fernández-Zacarías, Francisco; Jara-Muñoz, Edgar; Hernández-Molina, Ricardo (Frontiers in Pediatrics, 2021)
Low frequency noises are predominant in neonatal intensive care units (NICUs). Some studies affirm that neonates can perceive noises from 113Hz, and can therefore be affected by sound sources with high spectral content at low frequencies (e.g. incubator engine, air fan). Other studies suggest that reverberation amplifies noise within incubators. In this paper, the reverberation time (T, T30) within an incubator with standard dimensions was measured in one-third octave bands. To get reliable results, the T was measured in 15 positions at the neonate’s ear height, in a room with low T values (to reduce the influence of the room in the results), using an impulsive sound method. Results show a heterogeneous T distribution at the neonate’s ear height, with maximum average T differences between positions of 1.07 s. The highest average T of all microphone positions is 2.27 s at 125 Hz, an extremely high mean value for such a small space. As the frequency of electrical devices in America is 60Hz, some harmonics lay within the one-third octave band of 125 Hz, and therefore may create a very reverberant and inappropriate acoustic environment within the audible spectrum of neonates. As the acoustic environment of the incubator and the room are coupled, it is expected that the results are higher in the NICUs than in the room where the measurements were conducted, as NICUs are more reverberant. Therefore, it is recommended that the T will be limited in the international standards, and that incubator designers take it into account.